Unrequited interdependence? The Anglo-American collision over the supply of missiles to Israel, 1960–1962. (2nd July 2016) - Rumyantsev, Vladimir P.
Abstract : On 9 August 1962, the US unilaterally decided to sell Hawk ground-to-air missiles to Israel despite the preliminary agreement between Washington and London not to supply guided missiles to the Middle Eastern countries. This ignoring of British interests provoked a clash between Washington and London and the furious reaction of Harold Macmillan, who wrote probably most angry message in the history of Anglo-American relations. This article explores this clash as a significant component of the crisis of Anglo-American interdependence that influenced both the strategic partnership between the two Western powers and their relationship in the Middle East, where interdependence frequently became a myth.